Self-Compassion in Students Who Commit Non Suicidal Self-Injury - Oliva, Elisabeth; Benu, Juliana Marlin Y.; Anakaka, Dian L. (Journal of Health and Behavioral Science, 2025)
College students are an early adult age group that is vulnerable to emotional stress due to academic and non-academic demands. The inability to manage this stress can lead to maladaptive behaviors such as Non Suicidal Self-Injury (NSSI), which is an act of self-harm without suicidal intent. One approach that is considered effective in reducing NSSI behavior is self-compassion. Self-compassion consists of three main components, namely self-kindness, common humanity, and mindfulness. All components play an important role in building healthy emotional regulation, reducing the tendency to blame oneself, and improving the psychological well-being of college students. This article is a literature review that synthesizes various theories and previous research results to explain the relationship between self-compassion and NSSI behavior in college students. The findings show that high self-compassion is negatively correlated with NSSI behavior and acts as a psychological protector in dealing with stress and life pressures.